1992
DOI: 10.1590/s0004-282x1992000200014
|View full text |Cite
|
Sign up to set email alerts
|

Neuroesquistossomose medular avaliação clínico-laboratorial de 5 anos

Abstract: Schistosomiasis mansoni is an endemic disease in Brazil. Cases of nervous system schistosomiasis have been referred in our medical literature for the past forty years. In this report five cases of schistosomiasis of the spinal cord are studied. A review of the literature has been made and some clinical, laboratory and therapeutical aspects are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
3
5
0
3
Order By: Relevance
“…Occasionally, higher levels like T2-T3 may also be involved (Brito et al 1992, Nobre et al 2001, Santos et al 2001, Paz et al 2002. Like the observations made by the other authors, the present study found that the lower thoracic region of the spinal cord accounted for the largest proportion of cases (40.3%), followed by the lumbar region (15.8%).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Occasionally, higher levels like T2-T3 may also be involved (Brito et al 1992, Nobre et al 2001, Santos et al 2001, Paz et al 2002. Like the observations made by the other authors, the present study found that the lower thoracic region of the spinal cord accounted for the largest proportion of cases (40.3%), followed by the lumbar region (15.8%).…”
Section: Discussionsupporting
confidence: 86%
“…Literature data demonstrate that there is a clear predominance of schistosomiasis in men compared to women (Peregrino et al 1988, 2002, Brito et al 1992, Nobre et al 2001, Santos et al 2001. In the present study, among the patients with SMR, 66.2% were male.…”
Section: Discussionsupporting
confidence: 49%
“…The predominance of males and the age range from 20 to 50 years (Table 1) is according to the results previously reported in several other studies 4,10,18,[20][21][22] . The predominance of males is attributed to a great exposition in the environment 23 , added to professional activities that increase the intraabdominal pressure 4 .…”
Section: Discussionsupporting
confidence: 88%
“…The most frequent clinical findings, paraparesis, lower limb pain and urinary retention, and the frequency of paraplegia (13.5%), (Table 2) are consequences of the commonest location of the lesion of SCS, that is, conus medullaris and equine cauda 4,20 . The functional disturbances may be restrictive or disabling.…”
Section: Discussionmentioning
confidence: 99%
“…Ocorre principalmente na medula espinhal 10 , sendo responsável por cerca de seis 27 a 13,4% 7 das mielopatias nas áreas endêmicas, não ultrapassando de 200 o número de casos descritos na literatura 17 .…”
Section: Relato De Caso/case Reportunclassified